2011 IEEE International Conference on Communications (ICC) 2011
DOI: 10.1109/icc.2011.5963256
|View full text |Cite
|
Sign up to set email alerts
|

Network Coding-Based Cooperative ARQ Scheme

Abstract: Abstract-In this paper we introduce a novel Automatic Repeat reQuest (ARQ) scheme for cooperative wireless networks. Our scheme adopts network coding techniques in order to enhance the total bandwidth of the network by minimizing the total number of transmissions. The performance of the proposed approach is evaluated by means of computer simulations and compared to other cooperative schemes, while an analytical solution is provided to validate the results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For the two-way relaying scenario, several IEEE 802.11-compatible RANC ARQ protocols with single or multiple relays are proposed in [30]- [32], which are shown to outperform C-ARQ protocols in terms of throughput and total delay through simulation and analytical results. These analyses in [30]- [32] focus on the saturation situation where…”
Section: Related Workmentioning
confidence: 99%
“…For the two-way relaying scenario, several IEEE 802.11-compatible RANC ARQ protocols with single or multiple relays are proposed in [30]- [32], which are shown to outperform C-ARQ protocols in terms of throughput and total delay through simulation and analytical results. These analyses in [30]- [32] focus on the saturation situation where…”
Section: Related Workmentioning
confidence: 99%
“…One of them allows two overlapping transmissions from the source and Nikolaos one relay, thus leading to a full-duplex operation, although inter-relay interference (IRI) degrades the reception of the source's signal. Recently, network coding was proposed for cooperative relaying networks [8] in order to reduce the number of transmissions when erroneous packets are received at the destination, thus increasing the spectral efficiency of the communication. In what follows, a literature review for the main fields which constitute the basis of this work is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies show that wireless networks using NC give better throughput even though the complexity of the system increases. A novel Automatic Repeat reQuest (ARQ) system for cooperative wireless networks is introduced by Antonopoulos et al [12] in 2011, where cooperative and network coding techniques are combined in order to enhance the system's performance. They are able to obtain 85% bandwidth improvement due to the reduction of the total number of transmissions.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [13] propose system for wireless broadcast system based on the random network coding using two-State Markov Chain to model the channel. The authors analyze the throughput of a typical SR-ARQ using; Linear Network Coding (LNC) and Random Network Coding (RNC) and it is found that random network coding gives better throughput, especially in the case of a system with a large Algorithm 1: Pseudo-code for SW ARQ-NC used in protect [8] 1: pktCount ← 0 2: clear buffer 3: while (pktCount < n) do 4: wait for packet 5: buffer ← packet 6: pktCount ← pktCount + 1 7: end while 8: Matrix ← generated Vodermonde Matrix(buffer) 9: i ← 0 10: while (i ≤ pktCount) do 11: reply ← transmit(Matrix[i]) 12: end while number of receivers. Liu et al [14], introduce NC-ARQ system based on Two-State Markov channel for Cognitive Radio (CR) broadcast, where lost packets are XORed by CR base-station forming a new packet.…”
Section: Related Workmentioning
confidence: 99%